KEBEBASAN PEREMPUAN DALAM WACANA ETIKA SOSIAL - Achmad Charris Zubair (Litbang STFT Widya Sasana Malang, 2003)
Every human being is born free. The human freedom flows from his/her natural existence. In society it is not always that the natural freedom of woman is recognized. The article searches carefully the philosophical ethics of women’s freedom. It asserts that the problem of women’s freedom is not really in the philosophical but rather the social point of view. The arguments put forward are based especially on philosphical and theological perspectives of Islamic world.